2020
DOI: 10.1086/709913
|View full text |Cite
|
Sign up to set email alerts
|

The Purpose of Senatorial Grandstanding during Supreme Court Confirmation Hearings

Abstract: US Supreme Court confirmation hearings provide senators with an opportunity to engage a potential justice on a nationwide stage. Senators probe for information about future behavior on the bench. Nominees work through the questions, oscillating between forthcoming and vague responses. Such behavior encourages popular narratives that characterize this intricate dance as a “vapid and hollow charade.” We challenge this wisdom and argue that senators use these hearings to provide meaningful representation to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A similar phenomenon may have occurred with the Supreme Court. Consider volatile confirmation hearings (Cameron et al, 2013; Collins & Ringhand, 2016; Schoenherr et al, 2020), and media coverage that (A) increasingly treats the Court like the elected branches (Hitt & Searles, 2018; Fogarty et al, 2020) and (B) prefers to cover dissensus over collegiality (Bryan & Ringsmuth, 2016; Denison et al, 2020). Also, recall recent hearings that include the use of the so-called “nuclear option,” and McConnell’s about-face on whether nominations should occur during presidential election years.…”
Section: Winners Losers and Public Support For The Judiciarymentioning
confidence: 99%
See 1 more Smart Citation
“…A similar phenomenon may have occurred with the Supreme Court. Consider volatile confirmation hearings (Cameron et al, 2013; Collins & Ringhand, 2016; Schoenherr et al, 2020), and media coverage that (A) increasingly treats the Court like the elected branches (Hitt & Searles, 2018; Fogarty et al, 2020) and (B) prefers to cover dissensus over collegiality (Bryan & Ringsmuth, 2016; Denison et al, 2020). Also, recall recent hearings that include the use of the so-called “nuclear option,” and McConnell’s about-face on whether nominations should occur during presidential election years.…”
Section: Winners Losers and Public Support For The Judiciarymentioning
confidence: 99%
“…Margins of victory were once large and bipartisan, but now fall along party lines. The way senators interact with nominees is now predicated on partisanship (Boyd et al, 2018; Schoenherr et al, 2020). There is some evidence that recent nomination battles have weakened and polarized mass support for the judiciary (Carrington & French, Forthcoming; Krewson & Schroedel, 2020).…”
Section: Winners Losers and Public Support For The Judiciarymentioning
confidence: 99%
“…This approach is not limited to the Gorsuch confirmation hearing. Research has shown that opposition-party Senators asks more political and ideological questions of nominees than co-partisan Senators who tend to ask questions about qualifications and experience (Farganis and Wedeking 2014, 2011; Schoenherr, Lane and Armaly 2018). 5…”
Section: Motivated Reasoning and The Confirmation Processmentioning
confidence: 99%
“…On one side of this debate are those who find little value in the hearings and the potential for great harm to the Supreme Court's essential store of legitimacy (Kagan 1995; Zilis and Blandau 2021). On the other side are those who see the hearings as providing important public goods: during hearings senators represent constituent interests (Schoenherr, Lane, and Armaly 2020) and participants “engage in a debate about the meaning of the Constitution” (Collins and Ringhand 2013, 1). Carrington and French enter the discussion in a unique way, by arguing that the behavior of a nominee (rather than the partisan and political nature of a modern judicial confirmation hearing) harmed the Supreme Court's legitimacy.…”
mentioning
confidence: 99%